The Influence of Discipline and Motivation on Employee Performance at PT. Mahakam Branch Serang Banten - Rachmat Maulana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine the effect of discipline and motivation on employee performance at PT. Mahakam Serang Banten Branch. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that discipline has a significant effect on employee performance by 47.7%, hypothesis testing is obtained t count > t table or (7,578 > 1,998). Motivation has a significant effect on employee performance by 44.6%, hypothesis testing is obtained t count > t table or (7,128 > 1,998). Discipline and motivation simultaneously have a significant effect on employee performance with the regression equation Y = 8.276 + 0.427X1 + 0.370X2 and the contribution of the influence is 58.1%, hypothesis testing is obtained F count > F table or (42,912 > 2,750).